Elastic stable intramedullary nail combined with Kirschner wire (E-K) technique for treating pediatric distal tibial diaphyseal metaphyseal junction (DTDMJ) fractures - Liu, Yunlong; Ding, Sheng; Yang, Yancai (Frontiers in Pediatrics, 2024)
Objective:Elastic stable intramedullary nail (ESIN) is a commonly used method for treating diaphyseal fractures of the tibia, but its application in Distal Tibial Diaphyseal Metaphyseal Junction (DTDMJ) fractures has been a subject of controversy. This study aims to evaluate the clinical efficacy of the Elastic stable intramedullary nail-Kirschner wire (E-K) technique in treating pediatric DTDMJ fractures, providing better clinical decision-making for clinicians in diagnosing and treating such fractures.Methods:We conducted a retrospective analysis of patients aged 3 to 9 years who received treatment at our hospital from January 2019 to January 2021 for distal tibial diaphyseal metaphyseal junction (DTDMJ) fractures. Based on their surgical procedures, they were categorized into the Elastic Stable Intramedullary Nail -Kirschner wire group (E-K) and the ESIN group. Demographic data, surgical duration, clinical outcomes, complications, and imaging data were recorded.The study included a total of 57 patients, with 24 cases in the E-K group and 33 cases in the ESIN group. There were 30 males and 27 females. The average age